Chromosomal evolution of neotropical cichlids: The role of repetitive DNA sequences in the organization and structure of karyotype - Schneider, Carlos Henrique; Gross, Maria Claudia; Terêncio, Maria Leandra; Artoni, Roberto Ferreira; Vicari, Marcelo Ricardo; Martins, Cesar Henrique Rossinoli; Feldberg, Eliana (Reviews in Fish Biology and Fisheries, 2013)
Cichlids are important in the aquaculture and ornamental fish trade and are considered models for evolutionary biology. However, most studies of cichlids have investigated African species, and the South American cichlids remain poorly characterized. Studies in neotropical regions have focused almost exclusively on classical cytogenetic approaches without investigating physical chromosomal mapping of specific sequences. The aim of the present study is to investigate the genomic organization of species belonging to different tribes of the subfamily Cichlinae (Cichla monoculus, Astronotus ocellatus, Geophagus proximus, Acaronia nassa, Bujurquina peregrinabunda, Hoplarchus psittacus, Hypselecara coryphaenoides, Hypselecara temporalis, Caquetaia spectabilis, Uaru amphiacanthoides, Pterophyllum leopoldi, Pterophyllum scalare, and Symphysodon discus) and reexamine the karyotypic evolutionary patterns proposed for this group. Variations in some cytogenetic markers were observed, although no trends were found in terms of the increase, decrease, or maintenance of the basal diploid chromosome number 2n = 48 in the tribes. Several species were observed to have 18S rDNA genetic duplications, as well as multiple rDNA loci. In most of the taxa analyzed, the 5S rDNA was located in the interstitial region of a pair of homologous chromosomes, although variations from this pattern were observed. Interstitial telomere sites were also observed and appear to be involved in chromosomal rearrangement events and the accumulation of repeat-rich satellite DNA sequences. Our data demonstrated the karyotypic diversity that exists among neotropical cichlids, suggesting that most of this diversity is due to the repetitive sequences present in heterochromatic regions and that repeat sequences have greatly influenced the karyotypic evolution of these fishes. © 2012 Springer Science+Business Media B.V.
Keywords: Chromosome; Cichlid; Cytogenetics; Dna; Evolutionary Biology; Fluorescence; Genetic Marker; Genomics; Karyotype; Neotropical Region; Acaronia Nassa; Astronotus Ocellatus; Bujurquina; Caquetaia Spectabilis; Cichla Monoculus; Cichlasoma; Cichlidae; Cichlinae; Geophagus; Hoplarchus Psittacus; Hypselecara Coryphaenoides; Hypselecara Temporalis; Pisces; Pterophyllum; Pterophyllum Scalare; Symphysodon Discus; Uaru Amphiacanthoides